Pengaruh Edukasi pada Ibu Hamil dalam Upaya Pencegahan Stunting - Melissa Dwi Mayang Sari (Jurnal Medika Hutama, 2022)
Stunting is a significant nutritional problem related to the growth and development of toddlers. One aspect that affects the occurrence of stunting is from the condition of the mother before pregnancy, the nutrition of pregnant women, weight and height. One of the prevention of stunting can be through education for pregnant women so that it is hoped that changes in behavior will increase knowledge and attitudes in pregnant women. Study aims to determine the effect of education on pregnant women in preventing stunting. The literature study uses literature review articles and research articles in international and national journals in the last ten years. Results: From several studies that have been carried out, the authors conclude that education for pregnant women has a significant influence in preventing stunting. One of the improvement efforts needed to overcome stunting is through specific nutrition interventions for pregnant women